Effect of Photobiomodulation on Transforming Growth Factor-beta(1), Platelet-Derived Growth Factor-BB, and Interleukin-8 Release in Palatal Wounds After Free Gingival Graft Harvesting: A Randomized Clinical Study - Keskiner, Ilker; Lutfioglu, Muge; Aydogdu, Ahmet; Saygun, N. Isil; Serdar, Muhittin A. (MARY ANN LIEBERT, INC, 2016)
Objective: This study evaluated the impact of photobiomodulation (PBM) on the healing of the donor palatal area following free gingival graft (FGG) harvesting by examining changes in transforming growth factor (TGF)-beta(1), platelet-derived growth factor (PDGF)-BB, and interleukin (IL)-8 levels in palatal wound fluid (PWF). Material and methods: Thirty patients were selected and randomly assigned to receive PBM (laser group) or PBM sham (sham group) in the palatine area after FGG harvesting. Aneodymium-doped yttrium aluminumgarnet (Nd:YAG) laser (1064 nm) was applied to the test sites immediately after surgery and every 24 h thereafter for 4 days. PWF was collected on Days 7 and 12, and PWF TGF-beta(1), PDGF-BB, and IL-8 levels were analyzed by enzyme-linked immunosorbent assays (ELISA). Results: PWF TGF-beta(1), PDGF-BB, and IL-8 levels were significantly lower on Day 12 than on Day 7 for both groups. PWF TGF-beta(1), PDGF-BB, and IL-8 levels of the laser group were significantly higher than those of sham group on Day 7 (p < 0.05). PWF TGF-beta(1) levels were also significantly higher in laser group than in the sham group on Day 12

however, differences in PDGF-BB and IL-8 levels between groups on Day 12 were statistically nonsignificant. Conclusions: Observed increases in PWF TGF-beta(1), PDGF-BB, and IL-8 levels suggest that PBM may accelerate wound healing by stimulating production of selected mediators.